"If you really think it's that important—show me, don't tell me!". Issue 1 (14th June 2021) - Mize, Jennifer F.
Abstract: " Action speaks louder than words but not nearly as often ." Mark Twain : Effective process safety messaging supports, represents, and reinforces a strong process safety culture. However, no communication program or slogan can create a strong process safety culture. Organizations must invest the necessary time and resources to support process safety from the front lines to the board room. In order to establish, sustain, and improve process safety performance, organizations must identify and address situations that contradict their expectations and communication related to process safety. Employee engagement and commitment are only possible when sufficient incentives are provided. In other words, people will put the most effort into the activities that provide the most reward. Actions, particularly financial decisions, always speak much louder than words. Does the executive leadership have a long‐term strategy for investing in process safety? Is a demonstrated commitment to process safety necessary for career advancement? Are leaders rewarded for properly managing risk even when their decisions might have a short‐term negative impact on production? This paper will provide examples of situations that contradict an organization's process safety messaging and suggest best practices to address those situations.